Economic valuation of recreational resources in rural area - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (2012)
Quantitative studies on economic value of resources in rural area are carried out by determining the benefits gained by the tourists using the resources at the site. The value then can be used to imply the importance of conservation of resources to the communities. As many rural tourism destinations depend on the natural resources to be the main product of the tourism development, failure to take measures to conserve the natural resources in rural areas may cause overuse and sometime leading to irreversible damage. An alternative way to determine the value of resources is by using the travel cost method (TCM) which is an environmental valuation technique. TCM is site specific. Modification to the basic travel cost model (TCM) will account for other factors that may influence the demand for the rural tourism resources. The benefit from resources will be measured through the determination of a recreation demand curve for a particular site using the concept of consumer surplus. Hence, this paper intends to highlight the usefulness of economic valuation for a sustainable rural tourism setting and the biases of basic TCM which in turn induces the need for a modified TCM to obtain a perfect measure of the value of resources to tourist.